Hakikat Pendidikan dan Pembelajaran, serta Tanggung Jawab dan Standar Kompetensi Guru - Habsy, Bakhrudin All; ‘Ula, Elviana Rohmah Rosyidatul; Haq, Muhammad Akmal Ahsanul; Azizah, Taqiyyatul (Lembaga Yasin AlSys, 2024)
The purpose of this article is to provide an in-depth understanding of the nature of education and learning and the crucial role of teachers in the education process. It also aims to identify and outline the responsibilities and competency standards that teachers must possess in order to effectively support the achievement of educational goals. With this article, it is hoped that readers, especially prospective educators and education practitioners, will gain a clear insight into the importance of mastering teacher competencies in creating a quality learning process and building a generation with high character and competitiveness. Education is a dynamic process that aims to develop learners' potential holistically, including cognitive, affective and psychomotor aspects, to prepare them to become competent, responsible individuals who play a positive role in society. The essence of education lies in its efforts to form a whole person through a meaningful learning process, where learning is an activity designed to help students achieve certain understandings, skills and values. Teachers as learning facilitators have a great responsibility to create a conducive learning environment and encourage active involvement of learners. To fulfill this role, teachers are required to have competency standards that include pedagogical, personality, social, and professional competencies.